Research on Fuzzy Self-tuning Defrosting Technology of Air Source Heat Pump Air conditioners - 王铁军; 刘向农; 吴昊; 倪宜华; 高日新 (Zhileng xuebao, 2005)
Based on the experimental study on the processes of frosting and defrosting of the air conditioner when it works as heat pump, this paper reports a new technique of fuzzy self-tuning defrosting control, which can not only adapt to all weathers but also discern and correct the regulative parameter on line. This technique judges the point at which defrosting begins according to the difference between the evaporating temperature and the outdoor temperature and the ratio of variety of these two temperatures, and evaluates the quality of defrosting in terms of the defrosting time and the temperature of pipes as defrosting ends. Also it adjusts control parameter timely to achieve optimal heating effect. The results of experimental research show that this control method is reliable in a wide climate zone, and can grasp the point at which defrosting starts or ends, and defrosting is clean.